GivingCare - Empowering personal caregivers and personal assistants by developing technical, soft, and digital skills - Iwona Malinowska-Lipień; Ewa Kawalec-Kajstura; Iwona Bodys-Cupak; Alicja Kamińska; Anna Majda; Zuzanna Radosz-Knawa; Jose Manuel Silva; Eduardo Batalha; Manca Pajnic; Claire Champeix (Termedia Publishing House, 2023)
For a couple of years, Europe has been observing changes in the structure of the age of its population, which include a growing par-ticipation of elderly people and a decreasing percentage of people at productive age. The demand for care services is increasing, which results not only from the ageing society, but also from the large number of disabled people at post-productive age. The GivingCare project - Empowering caregivers and personal assistants by developing technical, soft, and digital skills - has taken place from the year 2020 to 2023 within the Erasmus+ programme, funded by the European Commission. The participants comprise 7 institutions from 5 European countries, namely Portugal, Spain, Slovenia, Poland, and Belgium. The leader of the project is the Santa Maria Health School in Portugal. The tasks realised within the GivingCare project are of international dimension. The area of the studies are target-chosen institutions from the participating countries, including healthcare facilities and universities. The main goal of the project was to strengthen the position of formal and informal caregivers for care-dependent people as well oth-er healthcare workers by developing technical, soft, and digital skills. The project fulfils the deficiency of higher education pro-grammes by creating and implementing innovative training programmes, as well as developing materials/resources, based on inde-pendent modules. The results and methodology of the GivingCare project aim at promotion of a holistic approach and popularisation of influence in particular target groups, i.e. the group of formal and informal caregivers.